Calcium carbonate precipitation by strain Bacillus licheniformis AK01, newly isolated from loamy soil: a promising alternative for sealing cement‐based materials. (8th November 2013) - Vahabi, Ali; Ramezanianpour, Ali Akbar; Sharafi, Hakimeh; Zahiri, Hossein Shahbani; Vali, Hojatollah; Noghabi, Kambiz Akbari
Abstract The relevant experiments were designed to determine the ability of indigenous bacterial strains isolated from limestone caves, mineral springs, and loamy soils to induce calcium carbonate precipitation. Among all isolates examined in this study, an efficient carbonate‐precipitating soil bacterium was selected from among the isolates and identified by 16S rRNA gene sequences as Bacillus licheniformis AK01. The ureolytic isolate was able to grow well on alkaline carbonate‐precipitation medium and precipitate calcium carbonate more than 1 g L−1. Fourier transform infrared (FTIR) spectroscopy, X‐ray diffraction (XRD) analyses, and scanning electron microscopy (SEM)/energy‐dispersive X‐ray spectroscopy (EDX) examinations were performed in order to confirm the presence of calcium carbonate in the precipitate and to determine which polymorphs were present. The selected isolate was determined to be an appropriate candidate for application in a surface treatment of cement‐based material to improve the properties of the mortar. Biodeposition of a layer of calcite on the surface of cement specimens resulted in filling in pore spaces. This could be an alternative method to improve the durability of the mortar. The kind of bacterial culture and medium composition had a profound impact on the resultant CaCO3 crystal morphology.